Entrepreneurship in policing and criminal contexts - Smith, Robert (Police researcher Scotland) (Contemporary issues in entrepreneurship research, 2021)
This volume of the "Contemporary Issues in Entrepreneurship Research" series is an invited expert contribution and is designed around a theme of growing importance in the entrepreneurship community namely that of entrepreneurship in policing and criminal contexts. The author was formerly a 'Career Constable' and also later a 'Professor of Entrepreneurship & Innovation' which makes him an acknowledged expert in both fields. This monograph explores and develops theory and practice in an area which has not received a lot of academic scrutiny. It will be useful to scholars of entrepreneurship who have limited knowledge of how entrepreneurship manifests itself in policing and criminal justice contexts; and to policing scholars and practitioners who have a limited knowledge of the power of entrepreneurship to revolutionize policing in the twenty-first century. It is specifically written with both audiences in mind and the need to be theoretical and robust. It is also timely given the changes brought about by an era of austerity followed by the Covid-19 pandemic and social upheavals which have challenged and changed the way we police an ever changing society.